Green synthesis and characterization of Fe2O3, ZnO and TiO2 nanoparticles and searching for their potential use as biofertilizer on sunflower - ÖZGÖREN CAN, TUĞBA; AYDİN, YILDIZ; ALTINKUT UNCUOĞLU, AHU (My University, 2024)
Nanoparticles, thanks to their superior properties such as large surface area and high reactivity, can be an alternative to traditional fertilizers for improving nutrient uptake. Furthermore, considering that chemical and physical synthesis methods require high energy consumption and cause environmental pollution, plant-mediated green synthesis of NPs has attracted great attention since it provides eco-friendly, biocompatible, and inexpensive solutions. In this present study, plant mediated green synthesis of Iron Oxide (Fe2O3), Zinc Oxide (ZnO) and Titanium Dioxide (TiO2) nanoparticles by using Laurus nobilis leaves (bay leaves) were carried out and their structural properties were characterized by UV visible spectra, Dynamic Light Scattering (DLS), Fourier Transform Infrared (FTIR), X-Ray Diffraction (XRD) and Transmission Electron Microscopy (TEM). UV spectrum and FTIR analysis exhibited characteristic peaks indicating the presence of the desired NPs, while DLS analysis and TEM images confirmed that synthesized particles are in nano-scale. The potential of nanoparticles as biofertilizer in agricultural uses were assessed by investigating their effects on sunflower growth in hydroponic system. TEM images of the NP applied plant tissues proved the uptake and translocation of NPs from root to leaf. Furthermore, Fe2O3, ZnO and TiO2 NP applications on sunflower up to 5 ppm generally improved physiological growth parameters such as root length, fresh weight and leaf surface area while 20 ppm of Fe2O3 and ZnO NPs application cause a significant decrease. Graphical abstract: (Figure presented.)
Keywords: Tıp; Tarımsal Bilimler; Ziraat; Bitki Koruma; Fitopatoloji; Yaşam Bilimleri; Moleküler Biyoloji ve Genetik; Sağlık Bilimleri; Temel Tıp Bilimleri; Biyokimya; Fizyoloji; Temel Bilimler; Medicine; Agricultural Sciences; Agriculture; Plant Protection; Phytopathology; Life Sciences; Molecular Biology and Genetics; Health Sciences; Fundamental Medical Sciences; Biochemistry; Human Physiology; Natural Sciences; Tarım Ve Çevre Bilimleri (Age); Yaşam Bilimleri (Life); Bitki Ve Hayvan Bilimleri; Biyoloji Ve Biyokimya; Moleküler Biyoloji Ve Genetik; Bitki Bilimleri; Agriculture & Environment Sciences (Age); Life Sciences (Life); Plant & Animal Science; Biology & Biochemistry; Molecular Biology & Genetics; Plant Sciences; Physiology; Moleküler Biyoloji; Bitki Bilimi; Molecular Biology; Plant Science; Metallic nanoparticle; Nanofertilizer; Plant mediated green synthesis; Sunflower